Mechanical strength of biliary defect closure after topical sealing: comparison of four sealants in a porcine model - Saeedi, Mohammed al; Fonouni, Hamidreza; Kashfi, Arash; Ghamarnejad, Omid; Majlesara, Ali; Soleymanzadeh Gharabaghi, Negin; Stahlheber, Oliver; Kraus, Thomas W.; Mehrabi, Arianeb; Kulu, Yakup (Asian journal of surgery, 2019)
Background/Objective - Biliary leakage is a potential complication of liver resection and is still a concern. The aim of the present study was to evaluate the effectiveness of four routinely used sealants in preventing bile leakage under pressure from an induced perforation of the gallbladder in a porcine model. - Methods - Forty Landrace pigs were randomly assigned to one of five groups. These included a control group (n = 8) and one group each for the sealants TachoSil®, TissuCol Duo®, Coseal®, and FloSeal® (n = 8 per group). In the control group, the perforation was left unsealed. To evaluate the biliostatic potential of the sealants, we measured the pressure that was needed to induce leakage (mmHg) and the gallbladder volume (cc) at the time of leakage in each group. - Results - A significantly higher mean pressure was required to induce leakage in the sealant groups compared with the control group. However, the biliostatic effects were heterogeneous among the sealant groups. Sealants with the highest to lowest effectiveness were TachoSil, Coseal, TissuCol, and FloSeal. The mean gallbladder volume at the time of leakage also varied between sealant groups. - Conclusion - Biliostatic properties are markedly improved by the use of modern sealants compared with using no sealant. However, the advantages and disadvantages of using sealants should be carefully considered in each clinical situation. The effectiveness of the sealants should be evaluated in chronic and clinical studies.
Published online: 29 December 2018
Gesehen am 11.12.2019